Weakening self-control biases the emotional evaluation of appetitive cues. - Christian Dirk Wiesner; Christoph Lindner (PLoS ONE)
Exerting self-control in a first task weakens self-control in a second completely unrelated task (ego-depletion). It has been proposed that ego-depletion increases approach motivation which would amplify positive emotions to appetitive cues. Here we investigated the effect of the depletion of cognitive self-control on the subsequent emotional evaluation of appetitive cues. Participants of the depletion group copied a text omitting frequent letters and thereby exerting self-control to inhibit automated writing habits. Participants of the control group just copied the text. In a subsequent task participants had to rate valence and arousal of their responses to neutral vs. positive pictures of humans, animals, food, or sceneries. Ego-depletion caused more positive valence ratings of neutral pictures and lower arousal ratings of positive pictures. The findings do not support the notion that ego-depletion increases approach motivation in general. Rather they suggest that-without a specific motivational context-depletion of cognitive self-control differentially alters the immediate emotional evaluation of appetitive cues.